An Optimized Neural Network Classifier for Automatic Modulation Recognition - Li Cheng; Jin Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Automatic modulation recognition which is one of the key technologies in no-cooperative communications has extensive application prospects in civilian and military fields. The design of classifier played a decisive role in recognition results. The classifier based on back propagation (BP) neural network is better in the existing methods. However, the traditional back propagation neural network (BPNN) have some well-known disadvantages. This study investigates the design of a classifier for recognition of six common digital modulations. This classifier based on BP neural network trained by improved particle swarm optimization (PSO) which is applied as a local search algorithm to find the optimal weights and thresholds of BPNN. The simulation experiment results demonstrate that the proposed classifier has a higher recognition accuracy than other classifiers. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3930